Populations and Individuals in Heterokaryotic Fungi: A Multilevel Perspective. Issue 4 (October 2014) - Booth, Austin
Abstract : Among mycologists, questions persist about what entities should be treated as the fundamental units of fungal populations. This article articulates a coherent view about populations of heterokaryotic fungi and the individuals that comprise them. Using Godfrey-Smith's minimal concept of a Darwinian population, I argue that entities at two levels of the biological hierarchy satisfy the minimal concept in heterokaryotic fungi: mycelia and nuclei. I provide a preliminary answer to the question of how to understand the relation between these two populations. This article contributes to discussions about the nature of biological individuality, organismality, and evolutionary transitions.